ESG Investing: An analysis on the performance of sustainable ETFs - Prazeres, Filipe Tomás da Piedade (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management